Kajian Spasial Kebutuhan Sarana Pendidikan Tingkat SMAN Di Kota Kendari - Eka Apriana; La Ode Restele; Jamal Harimudin; Fitriani Fitriani; Hasbullah Syaf (Universitas Halu Oleo, 2022)
Kendari City is one of the regions with a fairly large population level with total population is 359.371 person. The rapid growth in Kendari city caused an increase total of population, so that the increase in educational facilities and infrastructure. The method used to identify the need for high school facilities in this study is the analysis of SNI No. 13-1733-2004 and Voronoi Diagram Analysis. The study aims to: (1) determine the distribution of senior high school educational facilities in the Kendari City in 2019; (2) determine the need for senior high school educational facilities in the Kendari City in 2019. The results of this study are: (1) the distribution of the number of school-aged population in Kendari city in 2019 as much 9.790 persons with the total area of buildings is 1.643 m² needs an area of 25.454 m² with a standard 2.6 m²/person; (2) the need for education facilities at the senior high school in Kendari City, namely (the number of schools, the number of classrooms, and the number of teachers) in the study area is still largely low, however the level of availability of educational service facilities have a high score, so that in planning, developing, and constructing of educational facilities can be evenly distributed in all areas of Kendari City.Keywords: Voronoi Diagram Analysis, Education, Facilities and InfrastructureKota Kendari merupakan salah satu wilayah dengan tingkat populasi yang cukup besar dengan jumlah penduduk 359.371 jiwa. Pesatnya pertumbuhan di Kota Kendari menyebabkan bertambahnya jumlah penduduk, sehingga semakin meningkatnya kebutuhan akan fasilitas sarana dan prasarana pendidikan. Penelitian ini bertujuan untuk: (1) untuk mengetahui persebaran sarana pendidikan tingkat SMAN di Kota Kendari pada tahun 2019 (2) untuk mengetahui kebutuhan sarana pendidikan tingkat SMAN di Kota Kendari pada tahun 2019. Metode yang digunakan untuk mengidentifikasi kebutuhan sarana pendidikan tingkat SMAN adalah analisis SNI No. 13-1733-2004 dan Analisis Diagram Voronoi. Hasil penelitian ini menunjukkan bahwa: (1) persebaran jumlah penduduk usia sekolah tingkat SMAN di Kota Kendari pada tahun 2019 sebanyak 9.790 jiwa dengan jumlah bangunan 1.643 m² membutuhkan luas lahan 25.454 m² dengan standar kebutuhan sarana 2,6 m²/jiwa; (2) kebutuhan sarana pendidikan tingkat SMAN di Kota Kendari, yaitu (jumlah sekolah, jumlah ruang kelas, dan jumlah guru) di daerah penelitian sebagian besar masih rendah, walaupun demikian tingkat ketersediaan fasilitas pelayanan pendidikan mempunyai nilai skor yang tinggi, sehingga dalam perencanaan, pengembangan, dan pembangunan fasilitas pendidikan bisa merata di semua wilayah Kota Kendari.Kata kunci: Analisis Diagram Voronoi, Pendidikan, Sarana dan Prasarana